2023
DOI: 10.1039/d2gc03512j
|View full text |Cite
|
Sign up to set email alerts
|

Progress in reaction mechanisms and catalyst development of ceria-based catalysts for low-temperature CO2methanation

Abstract: We present a detailed review on the mechanistic understanding and catalyst development of CeO2-based CO2 methanation catalysts. Current challenges for deeper investigations and future perspectives are presented as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 196 publications
0
13
0
Order By: Relevance
“…In addition, partially reduced CeO x is inactive towards CO 2 hydrogenation (Figure S14), indicating that Ce 3+ ‐O V pairs are not sufficient for methanation reaction. This observation put forward ionic Ni‐Ce 3+ pairs as efficient reaction sites, contrary to the commonly accepted notion that metallic Ni and Ce 3+ are the active sites for CO 2 hydrogenation [11, 16, 18, 21–23, 42, 44] . The rather unexpected reactivity scheme is interpreted on the grounds of first principles calculations combined with ambient pressure XPS experiments.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, partially reduced CeO x is inactive towards CO 2 hydrogenation (Figure S14), indicating that Ce 3+ ‐O V pairs are not sufficient for methanation reaction. This observation put forward ionic Ni‐Ce 3+ pairs as efficient reaction sites, contrary to the commonly accepted notion that metallic Ni and Ce 3+ are the active sites for CO 2 hydrogenation [11, 16, 18, 21–23, 42, 44] . The rather unexpected reactivity scheme is interpreted on the grounds of first principles calculations combined with ambient pressure XPS experiments.…”
Section: Resultsmentioning
confidence: 76%
“…Reducible oxides, such as TiO 2 and CeO 2 have been widely used as supports for CO 2 methanation and in almost all cases were found to enhance the catalytic performance as compared to more inert supports such as Al 2 O 3 or SiO 2 [8, 9] . Among the many reducible supports, CeO 2 has attracted strong interest in the field of CO 2 valorisation because Ce 4+ can be easily reduced to Ce 3+ and create oxygen vacancy (O V ) sites [10–12] . The combination of the above mentioned characteristics established CeO 2 ‐supported Ni catalysts as one of the most studied and promising candidates for the CO 2 methanation reaction [13, 14] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sabatier reaction, also known as CO 2 methanation (CO 2 + 4H 2 → CH 4 + 2H 2 O, Δ H 298 K = −165.0 kJ mol –1 ) is a highly exothermic process that is favored at low temperatures (<400 °C). The reaction is considered to be one of the promising technologies for power-to-gas because it can be conducted at moderate temperatures and ambient pressure, and the produced CH 4 can be injected into the existing natural gas grid for transportation or locally used. , Ni and Ru supported on reducible oxides are the most active catalysts for CO 2 methanation; important examples of these are discussed in this section. Ni-based materials are the most extensively studied catalysts because of their relatively low price. …”
Section: Methanation Reactionmentioning
confidence: 99%
“…7 In contrast, Ni-based catalysts are commonly used in CO 2 methanation due to their high binding strength of *CO. 8 The Ni(111) plane of Ni nanoparticles is suggested to be the primary facet for the *CO conversion pathway. 9 Sometimes, the interface between Ni and its supports (e.g., ZnO, 10 MgO, 11 and CeO 2 12 ) induces metal-support interactions (MSIs) to facilitate methanation. Vogt et al 13 have revealed the structure-activity correlation of Ni nanoclusters (1-7 nm) in CO 2 methanation.…”
Section: Introductionmentioning
confidence: 99%